Hunting coronavirus severe acute respiratory syndrome coronavirus 2 (2019 novel coronavirus): From laboratory testing back to basic research - Yang, De-Ming (J Chin Med Assoc, 2020)
The rapid spread of coronavirus disease 2019 (COVID-19) in many countries causes citizens of daily inconvenience and even life-threat for elderly population. The invasion of the main pathogen, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; 2019 novel coronavirus [2019-nCoV]), into human body causes different levels of impact to various patients. One of the most important issues for COVID-19 is how to defend this virus with the ability to foresee the infected targets. Thus, we maintain the quarantined essentially as for as others saved from COVID-19. So far, the routine laboratory test to confirm whether infected by SARS-CoV-2/2019-nCoV or not is through real-time reverse transcription polymerase chain reaction (rRT-PCR; quantitative polymerase chain reaction [qPCR]) with certain sequence regions that recognize SARS-CoV-2/2019-nCoV RNA genome. The heavy loading of rRT-PCR (qPCR) machine and handling labor have tight-packed the instruments as well as the manpower almost in every country. Therefore, the alternative approaches are eagerly waiting to be developed. In this review article, we sort out some state-of-the-art novel approaches that might be applied for a fast, sensitive, and precise detection of SARS-CoV-2/2019-nCoV not only to help the routine laboratory testing but also to improve effective quarantine.